0775 Impact of insomnia, depression and anxiety on adherence to upper airway stimulation for obstructive sleep apnea: ADHERE registry update. (25th May 2022) - Patil, Reena Dhanda; Ishman, Stacey; Chang, Jolie; Thaler, Erica; Suurna, Maria
Abstract: Introduction: Insomnia, depression and anxiety are common comorbid conditions in patients with obstructive sleep apnea (OSA) and can negatively impact positive airway pressure (PAP) therapy adherence. Subsequent intolerance to PAP may lead to surgical treatment such as upper airway stimulation (UAS). We sought to determine the impact of baseline insomnia, anxiety or depression on UAS therapy adherence using data from a large multi-center registry. Methods: The ADHERE registry collects information on patients undergoing UAS (Inspire Medical, Golden Valley, MN) including baseline history of insomnia, depression, anxiety and the Insomnia Severity Index (ISI) questionnaire. We determined overall prevalence of insomnia, depression and/or anxiety, as well as UAS adherence after 6 months of therapy in groups with insomnia, depression, anxiety or none of these conditions. Using ISI to quantify insomnia, adherence in patients with no/mild insomnia (ISI < 15) was compared to those with moderate/severe insomnia (ISI ≥ 15). Results: 1639 patients were included; 10% reported a history of insomnia, 23% depression and 16% anxiety. There was no difference in UAS adherence between groups with or without a history of insomnia, depression, or anxiety. A baseline ISI score was available in 470 patients with no history of insomnia, and in 81 patients with a history of insomnia. In patients with no history of insomnia, 59% had ISI scores ≥15, while in those with a history of insomnia, 85% had ISI scores ≥15 (p < 0.001). There was no difference in therapy usage between patients with ISI scores <15 and ≥15 (6.7 ± 2.2 hours/night versus 6.4 ± 2.5 hours/night, p = 0.5). Conclusion: This study examined the impact of insomnia, depression or anxiety on adherence to UAS therapy for OSA. Patients with and without these conditions had similar UAS adherence. We found that insomnia as objectively based on the ISI score may be underdiagnosed in UAS patients who have no subjective history of insomnia at baseline. Despite this, ISI severity did not impact UAS adherence. Longer term follow-up with serial ISI scores and adherence data is needed to further understand how insomnia severity impacts UAS therapy outcomes and usage. Support (If Any):